2012
DOI: 10.1039/c2sm25502b
|View full text |Cite
|
Sign up to set email alerts
|

How nanorough is rough enough to make a surface superhydrophobic during water condensation?

Abstract: Nanostructured surfaces which manifest superhydrophobic properties during water condensation have a potential to dramatically enhance energy efficiency in power generation and desalination systems. Although various such surfaces have been reported, their development has been fortuitous, not driven by an understanding of the underlying physical processes. In this work, we perform a comprehensive study of microscale water condensation dynamics on nanostructured superhydrophobic surfaces made using a variety of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
171
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(177 citation statements)
references
References 55 publications
(108 reference statements)
5
171
0
1
Order By: Relevance
“…Benefiting from the wellestablished top-down micro-and nanofabrication technologies, various silicon nanostructures (e.g., nanoneedles [71,90] and nanocones [69] ) and their combination with regular microstructures (e.g., micropillars [25,85] and micropyramids [84] ) have been successively made for creating bionic CMDSP surfaces, and the transport behaviors of condensate microdrops at the microscale showing the typical coalescence-induced self-propelling details of condensed microdrops on the nanoneedle surface. f,g) Reproduced with permission.…”
Section: Metal-based Cmdsp Surfacesmentioning
confidence: 99%
“…Benefiting from the wellestablished top-down micro-and nanofabrication technologies, various silicon nanostructures (e.g., nanoneedles [71,90] and nanocones [69] ) and their combination with regular microstructures (e.g., micropillars [25,85] and micropyramids [84] ) have been successively made for creating bionic CMDSP surfaces, and the transport behaviors of condensate microdrops at the microscale showing the typical coalescence-induced self-propelling details of condensed microdrops on the nanoneedle surface. f,g) Reproduced with permission.…”
Section: Metal-based Cmdsp Surfacesmentioning
confidence: 99%
“…Their study showed that these droplets can either grow above the structure forming a 'balloon' like PW droplet (Figure 3b), or laterally spread into the structure forming a highly adhered W droplet (Figure 3c) 54,55 . While the droplet morphology is dictated by the intricate liquid/structure interaction dynamics, it can be approximately predicted by comparing the energies of the non-equilibrium advancing Cassie and Wenzel states with a dimensionless energy ratio: (4) where r = 1 + πdh/l 2 is the surface roughness, and θ a is the advancing contact angle on a flat surface.…”
Section: Wetting Phenomenamentioning
confidence: 99%
“…[18][19][20][21][22][23] These studies are limited to silicon substrates, however, and are not suitable for scaled-up industrial applications. Therefore, it is highly desirable to develop hybrid surfaces that are compatible with materials commonly employed for heat transfer applications, such as copper.…”
mentioning
confidence: 99%
“…Combined with a faster growth rate for individual droplets, this ordered droplet nucleation process increases the probability for coalescence of multiple droplets in the interstices between micro-posts (in comparison to the random coalescence events that occur on the more homogeneous nano-structured surface). Second, the presence of nanoscale roughness on the hierarchical surface increases the local condensate droplet contact angle , [18,42,43] which reduces the work of adhesion ( ad W ) of the droplet to the surface…”
mentioning
confidence: 99%
See 1 more Smart Citation